Comparative accuracy of unenhanced and IV-contrast enhanced MDCT in detection of acute appendicitis in adult patients - Charuswattanakul, Sirivipa; Chulroek, Thitinan (Chulalongkorn Medical Journal, 2021)
Background: Computed tomography (CT) is the preferred imaging modality for suspected acute appendicitis. However, optimal CT technique remains controversial. Objectives: To compare the diagnostic accuracy of unenhanced CT with standard IV-contrast enhanced CT in the diagnosis of acute appendicitis in adult patients and whether body mass index (BMI) affects the diagnosis. Methods: A total of 209 patients (70 males and 139 females) with clinically suspected acute appendicitis underwent both unenhanced and IV-contrast enhanced CT with rectal contrast administration. We retrospectively reviewed radiographic findings of appendicitis, appendiceal visualization, likelihood of appendicitis and alternative diagnoses. Receiver operating characteristic (ROC) analysis, unpaired t - test and the Chi-square test were used. Results: One hundred seventeen patients underwent appendectomy with definitely diagnosed appendicitis in 114 (54.5%) patients. Areas under the ROC curves were 0.88 (95% CI; 0.83 -0.92) for unenhanced and 0.92 (95% CI; 0.88 - 0.95) for enhanced CT without significant difference (P = 0.07). Sensitivity, specificity and diagnostic accuracy for unenhanced scan were about 86.7%, 88.5% and 87.6% compared with 93.9%, 89.5% and 91.9% for enhanced scan. Scores for visualization of the appendix were significantly higher in enhanced scan than in unenhanced scan of patients with normal BMI (P = 0.0002). Conclusions: Unenhanced CT has comparable diagnostic performance with enhanced CT for diagnosing acute appendicitis, regarding of BMI. However, diagnostic confidence and visualization of the appendix in normal BMI patients and alternative diagnoses tend to be compromised on unenhanced CT. Therefore, IV-contrast enhanced CT may be considered for detection of appendicitis, especially in normal BMI patients.